Analisis Klasifikasi Hipertensi dan Gangguan Fungsi Kognitif pada Lanjut Usia - Mayang Sari Ayu (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Hypertension is an increase in blood pressure which can interfere with the circulation of blood flow in the brain region so that it is at risk of cognitive dysfunction. Elderly people are prone to cognitive impairment. The five cognitive impairments include concentration, language, orientation, memory, and attention. The research objective was to analyze the correlation between hypertension classification and cognitive dysfunction in the elderly. This type of research is observational analytic using cross sectional design. The sample consisted of 65 hypertension patients consisting from 42 men and 23 women from 3 health centers in Medan City. Samples were taken by purposive sampling technique, namely hypertensive patients from secondary data of more than 5 years and received regular treatment of antihypertensive drugs from medical records of health centers. Measurement of the cognitive function of the interview using the Mini Mental State Examination screening examination. Univariate and bivariate data analysis used the chi-square test. There were 37 patients with grade I hypertension, 23 people with mild cognitive dysfunction and 14 severe cognitive dysfunction. Meanwhile, there were 28 patients with grade II hypertension who had mild cognitive function disorders 11 people and 17 people with severe cognitive dysfunction. The results of the bivariate analysis showed that there was a relationship between the classification of hypertension and impaired cognitive function in the elderly where the p-value was 0.04 (p <0.05). There is a correlation between the classification of hypertension and impaired cognitive function in the elderly Keywords: Hypertension classification, Cognitive function disorders, Elderly